2012
DOI: 10.2527/jas.2011-4068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral meloxicam on health and performance of beef steers relative to bulls castrated on arrival at the feedlot1

Abstract: Castration in weaned calves is stressful and affects profitability by reducing ADG and increasing susceptibility to disease. This study evaluated the effect of meloxicam, a nonsteroidal anti-inflammatory drug (NSAID), on performance and health of calves received as steers compared with bull calves surgically castrated on arrival at the feedlot. British × Continental bulls (n = 145) and steers (n = 113; BW = 193 to 285 kg) were transported for 12 h in 3 truckloads (d 0), weighed, and randomly assigned to receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 20 publications
2
40
1
Order By: Relevance
“…11 Scoring systems that assign a value based on degrees of illness are relatively common, 12 and are frequently used in disease research. 3,10,13 Even when quantitative measurements, such as rectal temperature, are combined with subjective assessment, the final disease classification remains subjective. 14,15 This subjectivity may impact how the results are interpreted if the CIS is used as one of the criteria in a treatment or preventative health program.…”
Section: Observer Monitoring Clinical Illnessmentioning
confidence: 99%
“…11 Scoring systems that assign a value based on degrees of illness are relatively common, 12 and are frequently used in disease research. 3,10,13 Even when quantitative measurements, such as rectal temperature, are combined with subjective assessment, the final disease classification remains subjective. 14,15 This subjectivity may impact how the results are interpreted if the CIS is used as one of the criteria in a treatment or preventative health program.…”
Section: Observer Monitoring Clinical Illnessmentioning
confidence: 99%
“…The study animals were 40 18-month-old Merino ewes with an average weight of 31.4 ± 0.5 kg.Methods Treatment was given orally at 24 h intervals for 6 days at dose rates expected to achieve therapeutic levels in sheep: carprofen (8.0 mg/kg), ketoprofen (8.0 mg/kg) and flunixin (4.0 mg/kg). Oil of turpentine (0.1 mL) was injected into a forelimb of each sheep to induce inflammation and pain; responses (force plate pressure, skin temperature, limb circumference, haematology and plasma cortisol) were measured at 0, 3,6,9,12,24,36, 48, 72 and 96 h post-injection. NSAID concentrations were determined by ultra-high-pressure liquid chromatography.…”
mentioning
confidence: 99%
“…Literature on the efficacy of orally administered NSAIDs in sheep is limited, although this route has been examined in cattle. 23,24 Odensvik reported that the bioavailability of flunixin when administered orally as granules to cattle was 60% of that attained following intravenous injection. 25 This reduced bioavailability is probably related to the influence of the rumen 26 and has led others to double the dose used non-parenterally in studies of orally delivered NSAIDs in cattle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In livestock species, substance P has been used as an indicator of physiological response to painful procedures, such as dehorning and castration (Coetzee et al, 2008;Coetzee et al, 2012aCoetzee et al, , 2012b. This study showed no difference in SUBP between LSH and AH cattle or between NEXH and EXH cattle, but this does not necessarily indicate a lack of pain, as not all studies of painful procedures show a difference in SUBP (Mintline et al, 2014).…”
Section: Discussionmentioning
confidence: 61%